Developing the capacity of young One Health professionals in Southeast Asia - International Livestock Research Institute (International Livestock Research Institute, 2021)
Young professional from Southeast Asia have benefitted from capacity development in One Health under the ILRI and Southeast Asia One Health University Network (SEAHOUN) collaboration. Some of the professionals share their experiences from the program in this film. The fellowship is funded by the United States Agency for International Development (USAID) through the One Health Workforce-Next Generation project.